Chemical Profiling, Molecular Docking, and Antidiabetic Activity of Basilicum polystachyon Leave Methanol Extract - RAIHAN, Muhammad; TUKIRAN, Tukiran; DEWI SAPUTRI, Ratih; AMBAR WATI, First; DWIYANTI, Firamita (Iraqi Journal of Science, 2025)
Diabetes mellitus (DM) has become a significant global health concern due to its rapidly rising prevalence, coupled with the considerable side effects and risks associated with antidiabetic medications. Natural products are the main source of drug discovery which are believed to have lower side effects and toxicity than synthetic drugs in clinical treatments. The objective of this study was to reveal the antidiabetic activity of Basilicum polystachyon (Lamiaceae) as a potential medicinal plant, along with its chemical profile to solve the problem of this disease. Based on these results, 103 individual compounds were identified in the methanol extract of this plant. Molecular docking simulations revealed several major compounds with good binding energies, indicating that these compounds were potential as α-glucosidase inhibitors. While in vitro enzymatic assay showed that the methanol extracts had weak antidiabetic activity with IC50 value 289.61 µg/mL. However, considering the long-term effects of synthetic drugs in the body, this plant could be a potential source of a natural antidiabetic agent.